2011
DOI: 10.1136/jnnp.2010.222232
|View full text |Cite
|
Sign up to set email alerts
|

Death after head injury: the 13 year outcome of a case control study

Abstract: Head injury is associated with increased vulnerability to death from a variety of causes for at least 13 years after hospital admission. There is a need to understand how head injury influences mortality, particularly in younger adults and after mild head injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
90
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(103 citation statements)
references
References 29 publications
9
90
4
Order By: Relevance
“…In a recent 13-year follow-up of their TBI cohort, McMillan and co-workers confirmed the significantly increased mortality rates, independent of trauma severity beyond the first year after injury (McMillan et al, 2011). Mortality rates were particularly high in younger TBI patients, with death rates more than six times higher in patients aged 15-54 years than in community controls matched for age, gender, and deprivation; and more than twice as high as in a second control group matched for duration of hospital admission caused by an injury unrelated to the TBI (McMillan et al, 2011).…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…In a recent 13-year follow-up of their TBI cohort, McMillan and co-workers confirmed the significantly increased mortality rates, independent of trauma severity beyond the first year after injury (McMillan et al, 2011). Mortality rates were particularly high in younger TBI patients, with death rates more than six times higher in patients aged 15-54 years than in community controls matched for age, gender, and deprivation; and more than twice as high as in a second control group matched for duration of hospital admission caused by an injury unrelated to the TBI (McMillan et al, 2011).…”
Section: Introductionmentioning
confidence: 55%
“…Mortality rates were particularly high in younger TBI patients, with death rates more than six times higher in patients aged 15-54 years than in community controls matched for age, gender, and deprivation; and more than twice as high as in a second control group matched for duration of hospital admission caused by an injury unrelated to the TBI (McMillan et al, 2011). According to the authors, the pathomechanisms for the increased mortality rates remain unclear and require further study (McMillan et al, 2011).…”
Section: Introductionmentioning
confidence: 94%
“…There is also a much broader inference of a type II error being committed by Rohling et al as they completely ignore all of the collateral information directly implicating non-cognitive residual deficits that may accompany mTBI that are not measured by neuropsychological tests. For example, in a truly prospective longitudinal investigation that has been ongoing for over 13 years, investigators as the University of Glasgow have shown that not only do a substantial number of mTBI patients end up with disability, but mortality rates are substantially increased (McMillan, Teasdale, Weir, & Stewart, 2011), which may in part be related to cardiac autonomic dysfunction even in mTBI (see Hilz et al, 2011). Large-sample TBI studies find increased risk for post-traumatic epilepsy even in mTBI (Ferguson et al, 2010).…”
Section: Current Mtbi Meta-analyses Perpetuate Type II Statistical Errormentioning
confidence: 96%
“…Impaired CBFV modulation might, in turn, contribute to the pathophysiology of unexplained mortalities in this large group of traumatic brain injury patients. [46][47][48][49] In acute subarachnoid hemorrhages, increased sympathetic tone likely contributes to vasospasms, [50][51][52][53][54] and can be identified by routine TCD recordings with additional spectral analysis. Monitoring of sympathetic CBFV modulation might support therapeutic decisions.…”
Section: Discussionmentioning
confidence: 99%